Implikasi Perbedaan Usia dalam Perkawinan terhadap Hak dan Kewajiban Suami Istri menurut Hukum Islam - Hakim, Anwar (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyse the implications of age difference in marriage on the rights and obligations of husband and wife, with a focus on the aspects of maintenance, household leadership, harmony, and resolution of domestic conflicts according to Islamic law and religious court practices.The research method used is empirical research with a qualitative descriptive approach. Data were collected through interviews with married couples with significant age differences and through a document study of religious court decisions relating to age-difference marriages. The results show that age differences in marriage affect the pattern of household leadership, communication, and the division of roles in the family. In some cases, younger husbands tend to experience challenges in carrying out the role of head of the family, while older wives are more dominant in decision-making. Economic factors and the level of emotional maturity also play a role in determining household harmony. From the perspective of Islamic law, age difference is not a barrier in marriage, but it can be a source of conflict if there is no balance in carrying out the rights and obligations of husband and wife. The conclusion of this study is that marriages with significant age differences require a deeper understanding of the rights and obligations in the household in order to create balance and harmony. Therefore, pre-marital guidance and the active role of religious courts in providing legal advice for couples with significant age differences are needed.